2012
DOI: 10.1007/s00404-012-2282-x
|View full text |Cite
|
Sign up to set email alerts
|

The sexual abuse of female children in Hungary: 20 years’ experience

Abstract: Prevention requires a systematic and lifelong approach to educating children about personal space and privacy and is the responsibility of parents and professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Several studies have reported that the majority of attackers are male and generally (63.2–83.3%) known to or acquainted with the victim and that 16.4–27% of assailants are members of the family . In agreement with this, all the attackers in this study were male and 88.2% were known to the victim, while 10.2% were family members.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have reported that the majority of attackers are male and generally (63.2–83.3%) known to or acquainted with the victim and that 16.4–27% of assailants are members of the family . In agreement with this, all the attackers in this study were male and 88.2% were known to the victim, while 10.2% were family members.…”
Section: Discussionsupporting
confidence: 88%
“…Child sexual abuse may have adverse psychological effects in both the short term and in the long term as far as adulthood . Several studies have emphasized that a number of psychiatric disorders may develop, such as behavioral problems, compromised interpersonal relations, sexually oriented behavior, sexual dysfunction, engagement in high‐risk sexual behavior, substance dependence, suicidal thoughts or behavior, personality disorders, eating disorders, anxiety disorders, depression, dissociation, and post‐traumatic stress disorder (PTSD) .…”
mentioning
confidence: 99%
“…There are no Hungarian National or Country statistics obtainable. The incidence and nature of child sexual abuse in Hungary have not been researched, apart from a recent study that investigated sexual abuse in only female children [ 26 ] and some unscientific evidence from split sources.…”
Section: Introductionmentioning
confidence: 99%
“…The abuse had occurred on multiple occasions in 29 % of the cases. 3 The occurrence rate of abuse was highest in the summer season (54%). 4 About 90% of survivors on a college campus know the person who assaulted them.…”
Section: Introductionmentioning
confidence: 96%